PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. TUKADMAS GC KOTA BIMA - Pratama, Yudi; Jaenab, Jaenab (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
This study aims to determine the effect of compensation and work disipline on emloyee perfomance at PT. Tukadmas GC Bima city. This research includes associative research. The population of this research are employees who work at PT. Tukadmas GC Bima city. The sample used in this study were 30 repondents. Research data obtained from questionnaires distributed to employees of PT. Tukadmas GC Bima city with the proportional sampling method. The instrument reliability test includes validity and reliability test. Classical assumption test. The hypothesis test used in multiple linear regression. The results o this study indicate that compensation has not signifikant effect on employee perfomance at PT. Tukadmas GC Bima city, Work disciplin has not significant effect on employee perfomance at PT. Tukadmas GC Bima city. Compensation and work disipline simultanneusly effect employee perfomance at PT. Tukadmas GC Bima city